รายงานการสอบสวนผู้ป่วยไข้หวัดนก รายที่ 1 และ 2 - พิทยาวงศ์อานนท์, จักรรัฐ; พุธวัฒนะ, พิไลพันธ์; กิจผาติ, รุ่งเรือง; นฤพนธ์จิรกุล, อุบลรัตน์; อารีย์โชคชัย, ดารินทร์; อึ้งชูศักดิ์, คำนวณ; ชุณห์สุทธิวัฒน์, ศุภมิตร (รายงานการเฝ้าระวังทางระบาดวิทยาประจำสัปดาห์, 2025)